Investigación sobre las concepciones de los estudiantes acerca de los estados de agregación y los cambios de estado - Borsese, A.; Lumbaca, P.; Pentimalli, R. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1996)
In this work the results of a test based on phase changes and the states of matter are discussed. They show heavy misconceptions in pupils, 15-16 years old, in the first two years of Italian Secondary Upper School. Pupils show best results when they must work with experimental situations but show difficulties to pass from verbal to graphical language.